Information Security Technology for Applications 15th Nordic Conference on Secure IT Systems, NordSec 2010, Espoo, Finland, October 27-29, 2010, Revised Selected Papers - Aura, Tuomas; Järvinen, Kimmo; Nyberg, Kaisa (Security and Cryptology ;, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 15th Nordic Conference in Secure IT Systems, NordSec 2010, held at Aalto University in Espoo, Finland in October 2010. The 13 full papers and 3 short papers presented were carefully reviewed and selected from 37 submissions. The volume also contains 1 full-paper length invited talk and 3 revised selected papers initially presented at the OWASP AppSec Research 2010 conference. The contributions cover the following topics: network security; monitoring and reputation; privacy; policy enforcement; cryptography and protocols.